2021
DOI: 10.1021/acs.macromol.1c01910
|View full text |Cite
|
Sign up to set email alerts
|

Blending Polyurethane Thermosets Using Dynamic Urethane Exchange

Abstract: Recycling crosslinked polyurethanes (PUs) is accomplished through mechanical or chemical processes that are energy-intensive or produce plastics of lesser value. Polymer recycling processes are notably intolerant of polymer mixtures, yet the ability to reprocess and compatibilize two or more crosslinked PUs together will make this process more amenable to mixed waste streams while offering an opportunity to tune the properties of the recycled polymer products. Here, we blend a rigid polyester PU and a soft pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…28−30 Although now largely investigated for many thermosets, this concept was only recently applied for PU foams by promoting transurethanization reactions during extrusion when the foam was loaded by a tin-based catalyst. 31,32 Unfoamed PHU networks with recycling ability were also reported when transcarbamoylation reactions, 33 eventually combined to other reversible reactions (e.g., transesterifications), 34,35 were induced in the presence of an appropriate catalyst during thermal treatment. 33−35 In PHU thermosets, the pending hydroxyl groups were responsible for the transcarbamoylation reactions and, thus, for the thermoset reprocessability.…”
mentioning
confidence: 95%
“…28−30 Although now largely investigated for many thermosets, this concept was only recently applied for PU foams by promoting transurethanization reactions during extrusion when the foam was loaded by a tin-based catalyst. 31,32 Unfoamed PHU networks with recycling ability were also reported when transcarbamoylation reactions, 33 eventually combined to other reversible reactions (e.g., transesterifications), 34,35 were induced in the presence of an appropriate catalyst during thermal treatment. 33−35 In PHU thermosets, the pending hydroxyl groups were responsible for the transcarbamoylation reactions and, thus, for the thermoset reprocessability.…”
mentioning
confidence: 95%
“…In two recent publications, Dichtel and co-workers combined the use of tin-catalyzed TC and industrially relevant polymer processing techniques, twin-screw extrusion (Figure ). , They demonstrated that PU thermosets and foams could be reprocessed into new thermosets via blending networks containing DBTDL or by postintroduction of DBTDL in the foams (2.3–3.1 wt %, 1.5 mol % to NCO groups). They initially evidenced the potential of this recycling strategy by incorporating sequentially “soft” PU networks into “hard” PU networks using coextrusion.…”
Section: Transcarbamoylation In Polyurethane Chemistrymentioning
confidence: 99%
“…[ 114 ] By dynamic urethane exchange reaction during twin‐screw extrusion, blends of rigid polyester PU and PU soft polyether PU networks yield materials with tunable mechanical properties that can vary from soft to elastomeric to rigid as a function of the feed composition. [ 115 ] Whether dynamic networks with the thermoresponsive bond exchange are, like static covalent networks, creep resistant and enable re‐processing of mixed waste streams, including formulated multicomponent thermosets, needs to be demonstrated.…”
Section: Mechanical Recycling and Energy Recoverymentioning
confidence: 99%